(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The article under discussion depicts the learning foreign languages from childhood. The article describes the benefits of studying second or third language at a young age and the ways of teaching it to children. The main attention is paid on the influences of learning foreign languages.